Radiographic and ultrasonographic alterations in the metacarpophalangeal joints in older horses do not necessariliy correlate to lameness - Schade J. (2023)
© 2023 Hippiatrika Verlagsgesellschaf. All rights reserved.Summary: Information regarding the behavior of different diseases in geriatric equines is scarce, including the ones related to the locomotor system, which is essential to the animal’s performance. The objective of this study was to evaluate the different types of alterations in the metacarpophalangeal joint (fetlock) in the thoracic limbs of geriatric equines and the frequency of which they occur. Furthermore, it was aimed to evaluate the scores of such lesions and their correlation to clinical manifestations. In this study, 39 mixed-breed equines were evaluated, all at a minimum age of 15 years (18,9±2,86 years old). Of those, 21 were females (53,8%) and 18 were geldings (46,2%). A clinical examination specific to the locomotor system was performed, followed by ultrasonographic and radiographic imaging of the metacarpophalangeal joint of the thoracic limb. For every image obtained, a scoring system was applied in accordance to the severity of the found lesion, such as in the radiographic image (0–4) and in the ultrasonographic image of the soft tissue (0–6) and bone (0–4). Thirteen equines (35%) presented lameness, out of which three (10%) were sourced in the metacarpophalangeal joint and 10 (25%) in other painful sites. All animals (39/39) showed alterations in the metacarpophalangeal joint through ultrasound evaluation and 35 (90%) and 38 (98%) in radiographic evaluation. Considering the injury scoring system for soft tissue, 46 of 78 forelimbs (46/78; 59%) were scored 0; 5/78 (6%) were scored 1; 4/78 (5%) were scored 2; scores 3 and 4 were not observed within the group; 21/78 (26%) were scored 5 and 3/78 (4%) were scored 6. For the scoring system for ultrasonographic alteration in bones, 22/78 (27,5%) were scored 0; 19/78 (23,8%) were scored 1; 32/78 (40%) were scored 2; 6/78 (7,5%) were scored 3 and 1/78 (1,3%) were scored 4. As for the radiographic evaluation, considering both limbs 2/78 (2,5%) were scored 0; 19/78 (23,8%) were scored 1; 13/78 (16,2%) were scored 2, 43/78 (53,8%) were scored 3 and 3/78 (3,7%) were scored 4. The main alterations observed in the study were related to degenerative chronic joint diseases. There was no relationship between the presence of lameness and the scores based on the image´s analysis. The absence of clinical manifestations in geriatric horses that were not being submitted to intense exercises does not exclude the presence of alterations in ultrasonographic and radiographic images of the metacarpophalangeal joint.